The level of synchronous thinking among Arabic language teachers and its relationship to their students’ achievement. (Journal of Misan Researches, 2024)
The current research seeks to identify the level of synchronous thinking among Arabic language teachers and its relationship to the achievement of their students. In order to achieve the objectives of the current research, the current study relied on the descriptive, correlational approach as an approach to the current research through a sample of Arabic language teachers in the First Rusafa Education Directorate, amounting to (100) teachers. In order to collect data and information about the level of synchronous thinking among Arabic language teachers, the scale (Abbas, 2020) was adopted, in addition to collecting data and information about academic achievement through their grades in the first course. After verifying the validity and reliability of the synchronous thinking scale among Arabic language teachers, it was Application of the current study The current study reached the following results:The level of simultaneous thinking among Arabic language teachers at the primary level was highThe level of achievement of sixth-grade primary school students in the Arabic language subject was highThere is a statistically significant relationship between Arabic language teachers’ synchronous thinking and their students’ achievement in the sixth grade of primary school.